Java™ Data Objects - Roos, Robin (Pearson Business, 2002)
Java Data Objects is a standardized Java API for object persistence. It facilitates the storage and retrieval of complex object models with various storage mechanisms, including both object and relational databases. Analysts agree that JDO's transparent persistence will accelerate software development and yield more flexible applications and object models. According to Infoworld , "The JDO standard promises to be a winner for business leaders and corporate developers alike. Unifying data access--that is, using familiar Java constructs to access information housed in relational databases, object databases, file systems, or even flash RAM--means that corporate applications will experience an increase in usability, portability and integration". This book is for Java developers, designers and architects with a good understanding of the Java language who wish to write applications that use JDO for persistence. Prior knowledge of JDBC and J2EE is not specifically required, but would help to accelerate the reader's understanding of JDO's relationship with these technologies. The companion CD-ROM includes the following JDO implementations:FastObjects, Kodo JDO, LiDO and OpenFusion JDO. 0321123808B08192002.